2013
DOI: 10.1089/jop.2012.0223
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Steroid Responsive Model of Ocular Inflammation in Rabbits Using an SLT Frequency Doubled Q Switched Nd:YAG Laser

Abstract: Commercially available SLT laser can be used to create a minimally invasive, steroid-responsive animal model of anterior uveitis with the potential for use in the evaluation and comparison of drugs intended to treat AC inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(23 reference statements)
0
7
0
1
Order By: Relevance
“…Increased levels of lipid peroxidase in aqueous humor and free oxygen radicals that are released from trabecular meshwork have been suggested to take part in inflammation occurring after SLT application [ 21 ]. In an animal experiment by Gulati et al [ 22 ] that investigated response to steroid treatment in anterior uveitis which was developed by applying laser to anterior surface of iris with SLT device, histopathological examinations revealed that there was pigment clumping at anterior surface of iris stroma, and that the changes were limited to anterior layers of iris. Additionally, after measurements conducted with flarimetry, they reported that laser applications resulted in anterior chamber inflammation that was responsive to steroids [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased levels of lipid peroxidase in aqueous humor and free oxygen radicals that are released from trabecular meshwork have been suggested to take part in inflammation occurring after SLT application [ 21 ]. In an animal experiment by Gulati et al [ 22 ] that investigated response to steroid treatment in anterior uveitis which was developed by applying laser to anterior surface of iris with SLT device, histopathological examinations revealed that there was pigment clumping at anterior surface of iris stroma, and that the changes were limited to anterior layers of iris. Additionally, after measurements conducted with flarimetry, they reported that laser applications resulted in anterior chamber inflammation that was responsive to steroids [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an animal experiment by Gulati et al [ 22 ] that investigated response to steroid treatment in anterior uveitis which was developed by applying laser to anterior surface of iris with SLT device, histopathological examinations revealed that there was pigment clumping at anterior surface of iris stroma, and that the changes were limited to anterior layers of iris. Additionally, after measurements conducted with flarimetry, they reported that laser applications resulted in anterior chamber inflammation that was responsive to steroids [ 22 ]. In our study, we observed ciliary injection and mild anterior chamber reaction in all groups on the first day, being more prominent in the Group B in which higher dose of laser was applied; and these signs disappeared in the examination at first week.…”
Section: Discussionmentioning
confidence: 99%
“…SLT induces minimal structural changes in the trabecular meshwork [1] in contrast to argon laser trabeculoplasty. Therefore, the liberation of humoral factors is thought to play a significant role in IOP reduction, which was also observed in animal models involving rabbits [2,3]. There were a few animal studies to suggest that the chemical components of the aqueous was modified after SLT [4,5].…”
Section: Introductionmentioning
confidence: 93%
“…На відміну від загальноприйнятої терапії увеїтів (Jamieson, Meckoll-Brinck, & Keller, 1989;Shelley et al, 2012;Gulati, Pahuja, Fan, & Toris, 2012;Movafagh, Heydary, Mortazavi-Tabatabaei, & Azargashb, 2011;Ahmad, 2018) з використанням кортикостероїдів, застосування яких супроводжується рядом небажаних побічних ефектів (гальмування регенерації, пригнічення імунної функції тощо), провели апробацію лікування токсикоалергічного увеїту із використанням нестероїдних протизапальних препаратів.…”
Section: вступunclassified